The course of the urban spaces if Paris in the novels: Rue des Boutiques Obscures and De Plus Loin de l'Oubli, by Patrick Modiano - Ribeiro, Rosária Cristina Costa; Barbosa, Sidney (Lettres Françaises, 2009)
Patrick Modiano’s work is still little known in our country. He has an extensive production which involves novels, autobiographies, short stories, plays and scripts. In 1978, he received the Goncourt prize, for his novel Rue des Boutiques obscures, the last of his novels about the theme of the Occupation. His novels portray the atmosphere of the 20th century in two main moments: the Nazi occupation and the youth of 1960. As for his treatment of the novel as a literary genre, there is the mixture of historical novel, nouveau roman, detective novel and autobiography, in an amalgam in which the category of the space stands out. With the contribution of those several types of novels, Modiano built a work that expresses the fragmentation of his spirit. Living in an obscure environment, the protagonists look for their identities, their past, and answers which remain undecipherable even after the end.